Investigation of the role of plasma channels as waveguides for laser-wakefield accelerators - Ibbotson, T; Bourgeois, N; Rowlands-Rees, T; Caballero, L; Bajlekov, S; Walker, P; Kneip, S; Mangles, S; Nagel, SR; Palmer, C; Delerue, N; Doucas, G; et al. (IOP Publishing, 2010)
The role of plasma channels as waveguides for laser-wakefield accelerators is discussed in terms of the results of experiments performed with the Astra-Gemini laser, numerical simulations using the code WAKE, and the theory of self-focusing and self-guiding of intense laser beams. It is found that at a given electron density, electron beams can be accelerated using lower laser powers in a waveguide structure than in a gas-jet or cell. The transition between relativistically self-guided and channel-assisted guiding is seen in the simulations and in the behaviour of the production of electron beams. We also show that by improving the quality of the driving laser beam the threshold laser energy required to produce electron beams can be reduced by a factor of almost 2. The use of an aperture allows the production of a quasi-monoenergetic electron beam of energy 520 MeV with an input laser power of only 30 TW. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.